The Political Economy of Skill Formation in a Rentier State: The Case of Oman - Langthaler, Margarita; Wolf, Stefan; Schnitzler, Tobias (International Journal for Research in Vocational Education and Training, 2022)
Context: Against a backdrop of dwindling oil resources and increasing unemployment rates, the government of Oman has set out to diversify its industry and establish a knowledge-based economy. In this context, forming a highly-skilled Omani workforce is considered to be of crucial importance. Yet, the national TVET system suffers from low social status, poor quality, and limited labour market connectivity. This paper offers an analysis of Oman's TVET system in the socio-economic and cultural context of a rentier state. Approach: We draw on the political economy of skills and socio-cultural approaches that understand TVET systems and the broader skills regimes in which they are embedded as part and expression of particular patterns of the social organisation of work. This helps to locate TVET systems' strengths and weaknesses in the context of their underlying social relations instead of considering them as mere dysfunctionalities at the systemic level. This paper draws on an unpublished study on TVET for industrialisation commissioned by an Omani line ministry in cooperation with an international organisation. For this study, the authors carried out a literature review, undertook two field trips to Oman in 2018 and 2019 and conducted forty semi-structured interviews with stakeholders from government, private companies, business associations, and TVET and higher education institutions. Findings: Our analysis highlights how skill formation in Oman is shaped by the socio-economic and cultural context of the Omani rentier state. First, the availability of cheap expatriate labour and Omanis' traditional preference for public sector jobs culminate in poor incentives for employing Omani nationals in the private sector. Second, reluctant employer attitudes towards national skill formation deepen quality issues in the TVET system, especially with regard to work-based training. This reinforces negative perceptions of the local workforce, which in turn contribute to biased employment patterns. Both social processes mutually reinforce each other, eventually preventing the emergence of strong national skill formation dynamics. Conclusions: While immediate structural change appears challenging, it is evident that reforms of the TVET system alone will not lead to its sustainable improvement. More research into how skill formation relates to Oman's specific socio-economic structures, how employment dynamics relate to educational credentials and how cultural traditions shape educational and work practices is needed.